2015
DOI: 10.1007/s00138-015-0717-7
|View full text |Cite
|
Sign up to set email alerts
|

On the value of the Kullback–Leibler divergence for cost-effective spectral imaging of plants by optimal selection of wavebands

Abstract: The practical value of a criterion based on statistical information theory is demonstrated for the selection of optimal wavelength and bandwidth of low-cost lighting systems in plant imaging applications. Kullback-Leibler divergence is applied to the problem of spectral band reduction from hyperspectral imaging. The results are illustrated on various plant imaging problems and show similar results to the one obtained with state-of-the-art criteria. A specific interest of the proposed approach is to offer the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…5, option 6), however, would need only pick and place, which is much faster. To monitor different traits of interest beyond morphological ones, additional sensors could be implemented: near-infrared spectroscopy to analyze the chemical content of seeds (Agelet and Hurburgh, 2014); chlorophyll fluorescence to score seed maturity and performance (Jalink et al, 1998); spectral imaging to classify common wheat (Triticum aestivum) and durum wheat (Triticum durum; Benoit et al, 2016); low-field NMR to measure both solid and liquid parts of a seed, as demonstrated for growing bean (Phaseolus vulgaris) pods (Windt and Blümler, 2015), or chemical components, such as lipids, carbohydrates, and proteins (Rolletschek et al, 2015); or x-ray CT to image internal seed structures, allowing, for example, the detection of internal defects of seeds (Stuppy et al, 2003;Belin et al, 2011;Yamauchi et al, 2012;Verboven et al, 2013). Further developments of phenoSeeder can be followed at www.phenoseeder.de.…”
Section: Discussionmentioning
confidence: 99%
“…5, option 6), however, would need only pick and place, which is much faster. To monitor different traits of interest beyond morphological ones, additional sensors could be implemented: near-infrared spectroscopy to analyze the chemical content of seeds (Agelet and Hurburgh, 2014); chlorophyll fluorescence to score seed maturity and performance (Jalink et al, 1998); spectral imaging to classify common wheat (Triticum aestivum) and durum wheat (Triticum durum; Benoit et al, 2016); low-field NMR to measure both solid and liquid parts of a seed, as demonstrated for growing bean (Phaseolus vulgaris) pods (Windt and Blümler, 2015), or chemical components, such as lipids, carbohydrates, and proteins (Rolletschek et al, 2015); or x-ray CT to image internal seed structures, allowing, for example, the detection of internal defects of seeds (Stuppy et al, 2003;Belin et al, 2011;Yamauchi et al, 2012;Verboven et al, 2013). Further developments of phenoSeeder can be followed at www.phenoseeder.de.…”
Section: Discussionmentioning
confidence: 99%
“…Although the developed system may be automated, their implementation on seed applications could be not straightforward if the relevant wavelengths have not been carefully selected or when the calibration procedure has not been precisely conducted [ 18 ]. Consequently, the procedure of selecting the ‘ optimal ’ wavelength is considered the most important step in developing and establishing an a high-throughput system that has the capability of performing the inspection and quality control decision in real time [ 111 ].…”
Section: Real-time Systems For High-throughput Applicationsmentioning
confidence: 99%
“…This requires the description of a communication channel with at least an input and an output characterized by their statistics expressed on a definite (discrete or continuous) alphabet of symbols together with a noise model. The modeling of imaging problems in the framework of information theory is an active research topic and was recently applied for instance to spectral reduction [5,6], observation scale optimization [7], image visualization [8,9] and multimodality imaging [10,11].…”
Section: Introductionmentioning
confidence: 99%